English Medium Instruction (EMI) lecturer support needs in Japan and China. (April 2022) - Galloway, Nicola; Ruegg, Rachael
Abstract: The internationalisation of higher education has resulted in a focus on English in non-Anglophone contexts and a boom in courses and programmes offered in English worldwide. Despite this growth in provision, a number of challenges have been identified with regards to English Medium Instruction (EMI) (Galloway et al., 2017 ), including a lack of suitable instructors and a lack of training and support for those transitioning to teaching their curricula in English. Drawing on questionnaires with students (n = 702) and teachers (n = 28), interviews with English for Academic Purposes (EAP) instructors (n = 10) and EMI content instructors (n = 17) and focus groups with EAP instructors (2) and content instructors (1), our study explores the types of instructors employed in EMI programmes in China and Japan, the characteristics that students consider important in instructors, and the support available. The results provide insights for faculty recruitment and training and overall EMI policy implementation.